Design of a trajectory contour controller for a dual‐axis precision motion stage based on improved iterative learning - Xiyou Chen; Tao Zhang; Bolun Wang; Jingzhe Fang; Hongyu Yan (IET Control Theory & Applications, 2023)
Abstract To solve the problem of contour error (CE) arising from the dual‐axis coupling of the X–Y coordinate planar motor stage under reciprocating motion conditions in integrated circuit (IC) manufacturing, the following two perspectives are considered: indirect intervention from a single‐axis servo tracking error (TE) control and direct intervention from a dual‐axis cross‐coupling control (CCC). An improved motion controller is designed using the iterative learning control (ILC) principle in conjunction with the motion characteristics of the dual‐axis mechanism. Specifically, the variable gain iterative learning controller with a variable forgetting factor (VFF‐VGILC) is designed to address the characteristics of single‐axis trajectory repetition and variable velocity planning in dual‐axis coupling. The significance of the VFF‐VGILC is to increase the servo control bandwidth of a single axis. On the other hand, the cross‐coupled iterative learning controller (CCILC) is designed on the dual‐axis cross‐coupling, while a pre‐compensation strategy is introduced in the CCC structure to form the pre‐CCILC. After experimental designing and testing are performed, the X–Y coordinate planar motor stage can effectively reduce the CE under various trajectory movements compared with the traditional controller. The trajectory curves drawn can meet the motion control requirements better and effectively enhance the motion control capability of the mechanism.